Living Capital and the Quantum Ethnography of Spider Goats: Review of Lisa Jean Moore, Our Transgenic Future: Spider Goats, Genetic Modification, and the Will to Change Nature - Fish, Kenneth (Humanimalia, 2023)
Review of:Lisa Jean Moore. Our Transgenic Future: Spider Goats, Genetic Modification, and the Will to Change Nature. New York: New York University Press, 2022. xviii + 214 pp. 23 b/w illus. $89.00 (hb), $30.00 (pb).